2019
DOI: 10.22454/fammed.2019.773836
|View full text |Cite
|
Sign up to set email alerts
|

Parental Leave Policies and Practices of US Family Medicine Residency Programs

Abstract: Background and Objectives: Adequate parental leave policies promote a supportive workplace environment. This study describes how US family medicine (FM) residency program parental leave policies compare to reported leave taken by residents and faculty. Methods: This is a descriptive study of questions from a 2017 Council of Academic Medicine Educational Research Alliance (CERA) survey of accredited US FM program directors. Results: The overall survey response rate was 54.6% (261/478). Paid maternity leave poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The known benefits of paid parental leave include decreased infant mortality, improved physical and mental health for mother and infant, increased maternal participation in the labor force, and enhanced morale of parents [ 7 – 10 ]. However, parental leave policies vary widely between institutions [ 11 ]. In an analysis of the top 50 medical schools with affiliated GME programs, 42% had paid leave policies for residents and fellows (average duration, 5.1 weeks), 42% did not provide any paid leave, and 22% offered state-mandated, partially paid leave [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The known benefits of paid parental leave include decreased infant mortality, improved physical and mental health for mother and infant, increased maternal participation in the labor force, and enhanced morale of parents [ 7 – 10 ]. However, parental leave policies vary widely between institutions [ 11 ]. In an analysis of the top 50 medical schools with affiliated GME programs, 42% had paid leave policies for residents and fellows (average duration, 5.1 weeks), 42% did not provide any paid leave, and 22% offered state-mandated, partially paid leave [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resident physicians, who have fatiguing work schedules, often have minimal paid maternity or paternity leave and would benefit from supportive return-to-work programs and policies. [112][113][114][115] Similar issues exist in veterinary residency programs. 116 It is important to support the needs of working parents, particularly during the post-partum and infancy stage, when working parents may be more sleep-deprived.…”
Section: Technologiesmentioning
confidence: 89%
“…Research could investigate the impact of maternity and paternity leave policies on workers’ health and safety. Resident physicians, who have fatiguing work schedules, often have minimal paid maternity or paternity leave and would benefit from supportive return‐to‐work programs and policies 112–115 . Similar issues exist in veterinary residency programs 116 .…”
Section: Research Prioritiesmentioning
confidence: 99%
“…[10][11][12][13] Studies specific to medical residents have found a lack of uniform policies regarding parental leave with regard to funding and also clinical coverage for new parents across several specialty training programs including surgery, OB-GYN, family medicine, and dermatology. [14][15][16][17] Trainees often report a perception of stigma and a lack of support for prospective and new parents, both by other trainees and by faculty. 18,19 Larger studies of parental leave policies across multiple specialties and institutions have similarly described a lack of standardized/formal GME parental leave policy across specialties and lack of specific references about the impact of parental leave on clinical training (length and eligibility for specialty boards).…”
Section: Discussionmentioning
confidence: 99%